The new altar guild book - Gent, Barbara; Sturges, Betty (Harrisburg, Pennsylvania : Morehouse Pub, 1996)
Originally published: The altar guild book. Wilton, Conn.: Morehouse-Barlow, cl982.
Includes bibliographical references.
Keywords: Altar guilds -- Episcopal Church -- Handbooks, manuals, etc; Episcopal Church -- Liturgy -- Handbooks, manuals, etc; Anglican Communion -- Liturgy -- Handbooks, manuals, etc